THE WAYANG GOLEK BROADCAST PROGRAM AS A STRATEGY EMPLOYED BY MAJA FM COMMUNITY RADIO TO PRESERVE CULTURAL EXISTENCE - Hendra Prasetia; Irfan Haniful Qoyyim; Zaenal Mukarom; Encep Dulwahab (FISIP Universitas Malikussaleh, 2026)
The rapid development of digital technology has significantly influenced the sustainability of traditional arts in Indonesia, including Wayang Golek as one of the most important cultural icons of Sundanese heritage. Amid changing media consumption patterns and declining public interest, innovative cultural preservation strategies are required to ensure the continuity of this traditional performance art. This study examines the cultural preservation strategy implemented through the